Irish London a cultural history 1850-1916 - Kirkland, Richard 1969- (Bloomsbury Academic, 2022)
"In the years following the Irish Famine (1846-49), London became one of the cities of Ireland. The number of Irish in London swelled to over 100,000 and from this mass migration emerged a distinctive and vibrant culture based on a shared sense of identity, history and experience. In this book, Richard Kirkland brings together elements in Irish London's culture and history that had previously only been understood separately or indeed largely overlooked (as in the case of women's' contributions to London Irish politics and culture). In particular, Kirkland makes resonant cultural connections between Irish and cockney performers in the music halls, Irish trade fairs, temperance marches, the Fenian Dynamite war of the 1880s, St Patrick's Day events, and the later cultural agitation of Revivalists such as W.B. Yeats and Katharine Tynan. Irish London: A Cultural History, 1850-1916 is both a significant contribution to our understanding of Irish emigrant communities in London at this time and an insightful case study for the comparative fields of cultural history and urban migration studies."